The Influence of Artificial Intelligence on Labor Markets - Zhuang Yanbin (SHS Web of Conferences)
Artificial Intelligence (AI) is fundamentally reshaping global labor dynamics, serving as both a transformative opportunity and a source of concern regarding employment stability. While its capacity to automate routine tasks threatens partial displacement in sectors like manufacturing and administrative services, the technology simultaneously stimulates demand for AI-related technical roles and hybrid professions requiring human-AI collaboration. This dual impact exacerbates income polarization, widening gaps between high-skilled professionals commanding premium wages and low-skilled workers facing heightened competition. To mitigate disruptions, multi-stakeholder coordination proves essential: governments must implement robust reskilling programs and adaptive labor policies, corporations should partner with educational institutions to align training with emerging skill requirements, while academia needs to cultivate agile learning ecosystems emphasizing critical thinking and digital literacy. Crucially, historical patterns suggest technological adoption ultimately generates more jobs than it eliminates. By prioritizing lifelong learning frameworks and fostering workforce adaptability, societies can transform AI from a displacement threat into an economic accelerant, ensuring labor market equilibrium and sustainable productivity growth amidst technological evolution.